(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2000)
In this paper we give a construction of a family of Baer subplanes of the Hughes plane H of odd square prime order q^2, q ≥ 5, which are not isomorphic to its well-known desarguesian Baer subplane H_0 [1, 5.4].